2014
DOI: 10.1371/journal.pone.0089967
|View full text |Cite
|
Sign up to set email alerts
|

The Curious Case of Benzbromarone: Insight into Super-Inhibition of Cytochrome P450

Abstract: Cytochrome P450 (CYP) family of redox enzymes metabolize drugs and xenobiotics in liver microsomes. Isozyme CYP2C9 is reported to be inhibited by benzbromarone (BzBr) and this phenomenon was hitherto explained by classical active-site binding. Theoretically, it was impossible to envisage the experimentally derived sub-nM Ki for an inhibitor, when supra-nM enzyme and 10X KM substrate concentrations were employed. We set out to find a more plausible explanation for this highly intriguing “super-inhibition” pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

6
1

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 26 publications
6
61
0
Order By: Relevance
“…From our studies, it is evident that P450 inhibition profiles could also be difficult to predict/interpret, with the erstwhile hypothesis as foundation. In this study, we have shown that both one electron and two electron reactions occurring in the aqueous phase is modulated by additives and therefore, it is only natural that the same effect be expected or amplified in the phospholipid interfaces where P450s catalyze reactions, This was in fact corroborated by our recent works [16,18,21]. Heme enzymes (and perhaps, other such redox enzymes) are unlike their classical counterparts in that they work via a "murburn" ('mured burning' or mediate unrestricted burning) mechanism [58] and not necessarily by 'induced fit' or 'lock & key' hypotheses.…”
Section: Mechanismsupporting
confidence: 80%
See 2 more Smart Citations
“…From our studies, it is evident that P450 inhibition profiles could also be difficult to predict/interpret, with the erstwhile hypothesis as foundation. In this study, we have shown that both one electron and two electron reactions occurring in the aqueous phase is modulated by additives and therefore, it is only natural that the same effect be expected or amplified in the phospholipid interfaces where P450s catalyze reactions, This was in fact corroborated by our recent works [16,18,21]. Heme enzymes (and perhaps, other such redox enzymes) are unlike their classical counterparts in that they work via a "murburn" ('mured burning' or mediate unrestricted burning) mechanism [58] and not necessarily by 'induced fit' or 'lock & key' hypotheses.…”
Section: Mechanismsupporting
confidence: 80%
“…Several other modulations and competitive inhibitions are also reported in heme-enzyme systems [49,50]. However, we had expanded the paradigm of redox enzyme "activations" when we reported the intriguing enhancement of reactions by low concentrations of known Type I & II hemoprotein binding "inhibitors" [14,21,22] and redox active molecules [15]. The current manuscript establishes the idea that trace amounts of additive molecules can also inhibit heme-enzyme mediated one-electron oxidations.…”
Section: Modulation Of Reactionssupporting
confidence: 60%
See 1 more Smart Citation
“…In the various hemeperoxiases and mixed oxidase cytochrome P450 systems, similar prevailing fallacies were pointed out and the kinetic/mechanistic phenomena were explained with murburn concept. 3,4,12,13,20,21…”
Section: Comparison Of Equilibrium and Kinetic Constants Of Cn With Omentioning
confidence: 99%
“…[1][2] Recently, an oxygen-centric mechanism called murburn (from 'mured burning') concept was proposed to explain the physiology of xenobiotic metabolism and cellular respiration. [3][4][5][6][7] The new proposal states that diffusible reactive oxygen species (DROS) generated at the mitochondrial complexes directly serve as the coupling agents of oxidative phosphorylation. It was proposed that cyanide ion-radical mediated catalysis, and not cyanide binding to heme (as currently held), is the primary rationale for cyanide lethality.…”
Section: Introductionmentioning
confidence: 99%